2020
DOI: 10.1002/ijc.33113
|View full text |Cite
|
Sign up to set email alerts
|

UBC12‐mediated SREBP‐1 neddylation worsens metastatic tumor prognosis

Abstract: Activation of sterol regulatory element‐binding protein 1 (SREBP‐1), a master lipogenic transcription factor, is associated with cancer metabolism and metabolic disorders. Neddylation, the process of adding NEDD8 to its substrate, contributes to diverse biological processes. Here, we identified SREBP‐1 as a substrate for neddylation by UBC12 and explored its impact on tumor aggressiveness. In cell‐based assays, SREBP‐1 neddylation prolonged SREBP‐1 stability with a decrease in ubiquitination. Consequently, NED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…A likely explanation for enhanced protein stability following the addition of NEDD8 to a substrate is that NEDDylation protects substrates from ubiquitination. Recently, Heo et al demonstrated that sterol regulatory elementbinding protein 1 (SREBP-1) stability is regulated by NEDDylation in multiple tumor cell lines [86]. Treatment with either MLN4924 or siRNA depletion of NEDD8, decreased levels of SREBP-1, presumably by allowing ubiquitination of SREBP-1.…”
Section: Protein Stabilizationmentioning
confidence: 99%
“…A likely explanation for enhanced protein stability following the addition of NEDD8 to a substrate is that NEDDylation protects substrates from ubiquitination. Recently, Heo et al demonstrated that sterol regulatory elementbinding protein 1 (SREBP-1) stability is regulated by NEDDylation in multiple tumor cell lines [86]. Treatment with either MLN4924 or siRNA depletion of NEDD8, decreased levels of SREBP-1, presumably by allowing ubiquitination of SREBP-1.…”
Section: Protein Stabilizationmentioning
confidence: 99%
“… Mo et al (2016) discovered that glycyl-tRNA synthetase (GRS) had the strongest correlation with mortality by analyzing the expression of 20 ARSs in 3557 breast cancer patients. Neddylation is a post-translational modification that attaches ubiquitin-like protein NEDD8 to its substrates and is implicated in cancer progression ( Heo et al, 2020 ; Zhou X. et al, 2020 ). In particular, GRS captured and protected NEDD8-conjugated Ubc12 (activated E2) by binding to the APPBP1 subunit of E1, thereby increasing the global level of neddylation ( Mo et al, 2016 ).…”
Section: Roles Of Arss In Cancermentioning
confidence: 99%
“…Deregulation of the neddylation pathway has been described in various pathological conditions. Focusing on the CLD context like liver fibrosis and HCC, both NAE1 and global protein neddylation expressions are upregulated (66,68). However, the initial triggering mechanism that overactivates neddylation pathways during CLD is not understood exactly.…”
Section: Overactivation Of Neddylationmentioning
confidence: 99%
“…Recently, it was reported that SREBP-1 can be neddylated by NEDD8 E3 ligase UBC12. Consequently, neddylation of SREBP-1 competing with its ubiquitination promotes the stability of SREBP-1 (68). Otherwise, liver kinase B1 (LKB1) and Akt kinases, critical regulators in proliferative metabolism of the liver, could be neddylated to enhance their stability.…”
Section: Neddylation and Hccmentioning
confidence: 99%